Comparison of Ig-M and some gastrointestinal disorders markers response to one-session continuous moderate training and high-intensity interval training in female athletes - Afshar Jafari; Maryam Taghizadfanid; Saeed Nikookheslat; Yousef Bafandetiz (Shahid Beheshti University, 2022)
Background and Purpose: Exercise-induced gastrointestinal syndrome" refers to disturbances of gastrointestinal integrity and function that are common features of strenuous exercise. Because of the ambiguities about the exercise-induced gastrointestinal disorders, the present study aimed to compare the responses of immunoglobulin M and some gastrointestinal disorders markers to one-session continuous moderate training and high-intensity interval training (MICT & HIIT) in female athletes.Material and Methods: To investigate the response of indicators related to the gastrointestinal syndrome, in a quasi-experimental design, thirty female athletes participated in three equal groups (MICT: n = 10, HIIT: n = 10, and control: n = 10). Athletes participated in the exercise test session on the 11th to 13th day of their menstruation after introductory course of training for two weeks. The training program in both MICT and HIIT groups included 7200 meters of treadmill running; So that the MICT group performed with an intensity of 70% VO2max and the HIIT group completed eighteen acute bout of 400 m runs at 110-100% VO2max. The control group was also at resting condition after taking the breakfast. Blood samples were collected before, immediately, and two h after the exercise protocols. Also, the symptoms of gastrointestinal symptoms were assessed by a questionnaire simultaneously. I-FABP, zonulin, LPS, and IgM amounts were measured using ELISA methods. All serum data expressed as mean ± SD and analyzed using repeated - measures analysis of variance and rank data of the symptoms of gastrointestinal symptoms analyzed using the Wilcoxon test at P ≤ 0.05. Results: Levels of I-FABP, LPS, and zonulin increased significantly (P < 0.05) after MICT and HIIT protocols, whereas Ig-M concentration decreased significantly (P < 0.05) after both types of exercise. Also, zonulin returned to baseline levels after 2 hours of HIIT (P > 0.05). Nevertheless, concentration of I-FABP 2 h after MICT, levels of zonulin and LPS 2 h after MICT and HIIT differences between with the control group was not significant (P < 0.05). However, acute decreased IgM and increased I-FABP, LPS and zonulin in responses to one-session MICT compare to HIIT protocols were not significant (P > 0.05).Conclusion: Given the present results, an acute MICT and HIIT session may increase damage, permeability, endotoxemia and decrease humoral immunity. However, gastrointestinal dysfunction due to HIIT exercise appears to be more pronounced which is not accompanied by symptoms of gastrointestinal discomfort.